Effect of insect-resistant transgenic maize on growth and development, utilization of nutrients and in vivo activity of the detoxification enzymes of the Asian corn borer, Ostrinia furnacalis (Lepidoptera: Pyralidae) - Min Juan SHI; Pei LING LU; Xiao Li SHI; Yi Zhong YANG (European Journal of Entomology, 2011)
There is little systematic research on the effect of transgenic maize expressing Bacillus thuringiensis (Bt) toxins on insect survival and the response in vivo of their detoxification enzymes. Results of laboratory bioassays indicate that the whorl leaves of transgenic maize lines G03-2396 and G03-2739 significantly affected the survival of neonate and third instar larvae of the Asian corn borer, Ostrinia furnacalis (Güenée). Neonate mortality two days after being fed on G03-2739 was 72.5% and exceeded 92.5% four days later. The percentage mortality of third instar larvae six days after being fed whorl leaves from G03-2396 exceeded 65%. The resistance of whorl leaves to insect attack was greater than that of maize-ears, but less effective against attacks by third instar larvae. Neonate development was more prolonged when they were fed on whorl leaves of both the transgenic maize lines. In contrast, low pupation (